1992
DOI: 10.1029/92wr00712
|View full text |Cite
|
Sign up to set email alerts
|

Does choice of multicriteria method matter? An experiment in water resources planning

Abstract: Many multiple criteria decision making methods have been proposed and applied to water planning. Their purpose is to provide information on tradeoffs among objectives and to help users articulate value judgments in a systematic, coherent, and documentable manner. The wide variety of available techniques confuses potential users, causing inappropriate matching of methods with problems. Experiments in which water planners apply more than one multicriteria procedure to realistic problems can help dispel this conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 26 publications
(18 reference statements)
5
61
1
1
Order By: Relevance
“…Studies in the assessment of GP techniques area are to a largest extent methodological and try to identify the pros and cons of different GP approaches to assess environmental policies. For example, Hobbs et al (1992) consider different WGP models to evaluate the level of understanding of multicriteria methods among water planners from the US Army Corps of Engineers. A similar experiment based on the same case study can be found in Goicoechea et al (1992).…”
Section: Applications In Economicsmentioning
confidence: 99%
“…Studies in the assessment of GP techniques area are to a largest extent methodological and try to identify the pros and cons of different GP approaches to assess environmental policies. For example, Hobbs et al (1992) consider different WGP models to evaluate the level of understanding of multicriteria methods among water planners from the US Army Corps of Engineers. A similar experiment based on the same case study can be found in Goicoechea et al (1992).…”
Section: Applications In Economicsmentioning
confidence: 99%
“…The AVF, which simply can be perceived as the normalized weighted summation of all criteria scores with respect to each alternative, is an easy to understand method. It is well perceived by water resources planners [Hobbs et al, 1992] and has been used by other researchers in water resources literature [Qureshi and Harrison, 2001;Huth et al, 2004;Fassio et al, 2005]. ELECTRE II was selected because it is conceptually different from the AVF in the way it solves the payoff matrix and ranks different alternatives.…”
Section: Impact Assessment (Scoring)mentioning
confidence: 99%
“…Variants of ELECTRE have been successfully used in water resources literature [Tecle et al, 1988;Hobbs et al, 1992;Roy et al, 1992;Raju and Duckstein, 2004]. ELECTRE II is a variant of ELECTRE family that produces a ranking of alternatives rather than indicating the most preferred.…”
Section: Electre IImentioning
confidence: 99%
See 1 more Smart Citation
“…• MCDA improves the justification of decisions It must be noted that MCDA does not claim to provide a "correct" or "true" system of weights or scores, as these are determined by the inputs of the stakeholders of the decision-making process (Hobbs et al, [18]; Stewart et al, [34,35]). The "correct" system reflects the trade-offs society is willing to make in any specific situation.…”
Section: Decision Support For Strategic Water Resource Managementmentioning
confidence: 99%